Bank Efficiency Analysis: Islamic Banks versus Conventional Banks in Turkey between 2011 and 2016. - HAMARAT, CAGLAR (2017)
This study investigates the efficiency of conventional and Islamic banks in Turkey from 2011 to 2016 using stochastic frontier analysis (SFA). The main objective of this paper is to analyse the cost efficiency of the Turkish banking system and to compare the efficiency of conventional and Islamic banks. Following the cost efficiency results obtained using the SFA intermediation approach, the Battese and Coelli (1995) model is used to determine efficiency factors in a one-step method in which several variables directly affect firm- and country-specific effects. The empirical analysis was based on a sample that compiled panel data for 23 continuously operating commercial banks and four Islamic banks. The efficiency estimation for each bank was calculated using three inputs – total interest expenses, personnel expenses, and other operating expenses – and three outputs: gross loans, off balance sheet items, and other earning assets specified under the intermediation approach through one-step input-oriented SFA. The one-step approach allows control of country- and firm-specific factors as well as Shariah-compliant banking directly in the estimated frontier allowing any differences related to technology and output that is the consequence of the differences in the operating characteristics of the two banking systems. The results of SFA indicate that the overall efficiency of Islamic banks is lower than the efficiency of conventional banks. Regarding the results, inflation and interest rate are statistically significant for the selected external variables and have a negative impact on the cost efficiency of Turkish banks, especially between 2012 and 2014.